PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Zhah Rotul Nikmah; Puji Winarko, Sigit; Faisol, Faisol (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This study aims to analyze the influence of financial ratios, including Profitability Ratio (Gross Profit Margin), Liquidity Ratio (Current Ratio), Solvency Ratio (Debt Ratio), and Activity Ratio (Inventory Turnover), on the financial performance of coal companies listed on the Indonesia Stock Exchange from 2019 to 2023. Financial performance is measured by Return on Assets (ROA). Using panel data regression with the Random Effect Model on 12 purposively selected companies with a total of 60 observation units, the results show that, partially, the profitability, liquidity, and solvency ratios have a significant effect on financial performance, while the activity ratio does not show a significant effect. Simultaneously, the four financial ratios significantly affect financial performance. The results are expected to aid company management, investors, and future researchers in evaluating financial performance in the coal industry.